The Role of Extracellular Vesicles as a Shared Disease Mechanism Contributing to Multimorbidity in Patients With COPD - Reid, Laura V.; Spalluto, C. Mirella; Watson, Alastair; Staples, Karl J.; Wilkinson, Tom M. A. (Frontiers in Immunology, 2021)
Chronic obstructive pulmonary disease (COPD) is one of the leading causes of death worldwide. Individuals with COPD typically experience a progressive, debilitating decline in lung function as well as systemic manifestations of the disease. Chronic conditions including cardiovascular disease, osteoporosis and diabetes are commonly observed in conjunction with COPD and increase the risk of hospitalisation and mortality. Central to the genesis of multimorbidity in COPD patients is a self-perpetuating, abnormal immune and inflammatory response driven by factors including ageing, pollutant inhalation (including smoking) and infection. As many patients with COPD have multiple concurrent chronic conditions, which require an integrative management approach, there is a need to greater understand common mechanisms contributing to multimorbidity. Recent evidence suggests that the intercellular transfer of extracellular vesicles (EVs) is an important method of local and distal cell-to-cell communication mediating both homeostatic and pathological conditions. EVs have been identified in many biological fluids and provide a stable capsule for the transfer of cargo including proteins, lipids and nucleic acids. Of these cargo microRNAs (miRNAs), which are short 17-24 nucleotide non-coding RNA molecules, have been the most extensively studied. There is evidence to support that miRNA are selectively packaged into EVs and can regulate recipient cell gene expression including major pathways involved in inflammation, apoptosis and fibrosis. Furthermore changes in EV cargo including miRNA have been reported in many chronic diseases and in response to risk factors including respiratory infections, noxious stimuli and ageing. In this review, we discuss the potential of EVs and EV-associated miRNA to modulate shared pathways and be a common mechanism that could contribute to the development of multiple chronic diseases. Further delineating the role of EV miRNAs in both pathological and protective processes in chronic diseases could not only serve to identify novel biomarkers but identify novel therapeutic targets. This could support new management strategies for multimorbid COPD patients.